Langgar and the Agency of Women in Developing Religious Literacy: A Research Based on Participatory in Southern Rembang - Ali Jafar (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2021)
This research explains the multiple barriers of women in rural villages in Southern Rembang, Indonesia. Beside economics and culture, they also face religious barriers in which religious learning and literacy are privileged to only certain people. Kajar is a village where Human Development Index is below the national level and women have dual roles as both domestic workers and family caretakers. Unfortunately, the poverty and lack of purpose in women’s education have limited women’s choices and voices.Through research-based on participation in making women agents of social-religious change, this research finds that women are robust agents for developing literacy based on langgar for their consistency and ability to influence their family, neighborhood, and society. The agencies of women are also going through making the langgar as ‘unofficial madrasa’ where children, both male, and female, are learning religious knowledge equally. Although the impact is not that instant, the agencies have slowly improved religious knowledge and perception of female religious education.